Pendaftaran Nomor Induk Berusaha Berbasis Online Single Submission Risk Based Approach di BUM Desa Semedi Karya, Desa Senganan, Penebel Tabanan - I Wayan Kartika Jaya Utama; I Made Sara; Cokorda Krisna Yudha (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Senganan Village is a village in Penebel District, Tabanan Regency with a population of 6,431 people, consisting of 3,186 males and 3,245 females, distributed across 12 Banjar Dinas. Senganan Village is one of the villages with great economic potential, and with this potential, the existence of the Village-Owned Enterprise (Bum Desa) becomes important to manage and utilize local resources. Senganan Village has the Semedi Karya Bum Desa, which has been established since 2014, but in recent times has faced several significant challenges that have disrupted business activities. The inactivity has resulted in incomplete business legality, especially regarding the registration of the Business Identification Number (NIB) that Bum Desa must have starting from 2023. Given the problems faced, the implementation of this community service activity is carried out using methods of socialization, training, technology application, mentoring, and program evaluation and sustainability. The result of this activity is that Bum Desa Semedi Karya is facing several issues, including legal cases involving previous management, a lack of understanding regarding the registration process for NIB based on OSS RBA, and unawareness of the benefits of business legality through NIB. To address this, socialization, training, mentoring, and post-training evaluation were conducted. Having an NIB also opens access to various facilities and government support, such as capital and training. However, the implementation of this system in Bum Desa Semedi Karya has not been fully realized due to inactivity in business over the past few years and the existence of legal cases that need to be resolved first. Once the legal issues are resolved, the NIB registration can be continued promptly